Wigner distribution function formalism for superconductors and collisionless dynamics of the superconducting order parameter: Сверхпроводимость и мезоскопические структуры - Amin, M.H.S.; Bezuglyi, E.V.; Kijko, A.S.; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
A technique for studying collisionless dynamics of a homogeneous superconducting system is developed which is based on Riccati parametrization of the Wigner distribution function. Thequantum evolution of the superconducting order parameter, initially deviating from the equilibrium value, is calculated using this technique. The effect of a time-dependent BCS paring interaction on the dynamics of the order parameter is also studied.